Innovative business services in creating competitiveness of small and medium-sized enterprises in Poland - Nowacki, R.; Wasilik, K. (Видавництво Львівської політехніки, 2016)
An important symptom of the changes taking place in the contemporary sector of services is the growth in importance of business services. Their development is connected with an ever complex course of economic processes and the increasing competition. Under the conditions of the quickly changing market, intense technical progress, ongoing labour division and being its effect of specialisation, the majority of economic entities, particularly in the SME sector, is not self-sufficient and must use specialist services. Reaching in this respect for innovative solutions may have caused increasing effectiveness of processes within the organisation and raising competitiveness. The subject matter of considerations in this article is just an analysis of the use by SMEs in Poland of business services and assessment of their innovativeness as well as its impact on SME competitiveness. Важливим проявом змін, що відбуваються в сучасному секторі послуг, є зростання значення бізнес-послуг. Їхній розвиток пов’язаний з усе склад нsiим перебігом економічних процесів і зростаючою конкуренцією. В умовах швидкоплинного ринку, інтенсивного технічного прогресу, поглибленого поділу праці та похідної з нього спеціалізації більшості економічних суб’єктів, особливо в секторі МСП, є несамодостатніми та повинні використовувати спеціальні послуги. Застосування в цьому відношенні інноваційних рішень може спричиняти підвищення ефективності процесів у межах організації і підвищення конкурентоспроможності. Предметом розгляду в цій статті є лише аналіз використання бізнес-послуг малими і середніми підприємствами в Польщі та оцінка їхньої інноваційності, а також їхній вплив на конкурентоспроможність малого і середнього бізнесу.
Інноваційні бізнес-послуги у формуванні конкурентоспроможності малих і середніх підприємств в Польщі
Keywords: business services; service innovativeness; SME; enterprises’ competitiveness; бізнес-послуги; інноваційність послуг; МСП; конкурентоспроможність підприємств